Niezgoda między szkołami gramatycznymi z Al-Basry i Al-Kufy na podstawie sporu o etymologię słowa ism - Grad, Jacek (Studia Azjatystyczne, 2017)
When it comes to Basran and Kufan grammarians, there is no dearth of studies, but nevertheless we are mostly left with rather general statements concerning the nature of both schools of Arab grammatical thought. In this article, after a short summary of the current state of research, an extract from a 12th century compilation of disputes between Basran and Kufan grammarians - Al-Insaf f i masa"il al-hilaf bayna al-basriyyin wa-al-kufiyyin by Ibn al-Anbari - is put under examination. The discussed extract is a chapter dedicated to the disagreement on the etymology of the word ism and it gives us a worthwhile overview on various aspects of medieval Arabic grammatical thought, and helps us understand the nature of the conflict between the two competing schools.